HOLIDAYS, TRADITIONS AND CUSTOMS OF THE UNITED STATES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article explores the rich tapestry of holidays, traditions, and customs prevalent in the United States. It delves into the diverse array of celebrations, ranging from nationally recognized holidays like Independence Day and Thanksgiving to culturally specific observances such as Hanukkah, Ramadan, and Diwali. The piece meticulously details the customs associated with each holiday, highlighting their historical significance and contemporary practices.